Christian Faith and University Life Stewards of the Academy (Springer International Publishing, 2018)
This book provides new insights on the unique role of graduate students within Christian higher education. Weaving together a variety of voices-doctoral students, new faculty, and seasoned scholars-with findings from empirical qualitative research, the book examines how faith and stewardship guide how they pursue scholarship and teaching as well as the academy's relationship to the church. The result of this examination is a coherent and thematic narrative that will appeal to Christian graduate students and new faculty seeking to enter the academy with a clear sense of purpose and responsibility. .